Design, Synthesis and Biological Evaluation of Tetrahydrodibenzo[b, g][1, 8]napthyridinones as Potential Anticancer Agents and Novel Aurora Kinases Inhibitors. Issue 14 (14th April 2021) - Chate, Asha V.; Tagad, Pramod A.; Bondle, Giribala M.; Sarkate, Aniket P.; Tiwari, Shailee V.; Azad, Rajaram
Abstract: Aurora kinases inhibitors A and B have elucidated a vital role within the carcinogenesis and metastases of assorted sort of cancer. Variety of novel methodologies of drug style and support of potential enzyme inhibitors square measure listed in clinical trials, probably there's no advanced clinical role for kinases because the key targets for developing drug than in cancer medical care until date. Therefore, we have designed and synthesized novel tetrahydrodibenzo[b, g] [1, 8]naphthyridinone molecules victimisation L‐Proline in ethanol as associate adept organocatalyst for one‐pot synthesis. This methodology is delicate, competent, high yielding, and also the product was directly crystallized from hot ethanol, in addition to this synthesized compounds were biologically evaluated for anticancer activity against human respiratory organ cancer (A549), human hepatocellular liver cancer (HepG2) and human cervical cancer animal tissue (HeLa) cells victimisation MTT assay victimisation VX‐680 as normal drug, specifically inhibiting Aurora A and Aurora B kinases. The compounds 4 f, 4 h and 4k were found to be sensible anticancer agents against the complete selected cancer cell lines. The compound 4k was found to be the foremost potent anticancer compound among the synthesized derivatives with IC50 value 16.22 μM, 20.14 μM and 5.32 μM against A549, HepG2 and Hela cell lines. The potent compounds 4 f, 4 h and 4k were specifically inhibiting Aurora A and Aurora B kinases. The compound 4k was found to be potent Aurora kinases substance with IC50 value 24 nM and 58 nM against Aurora A and Aurora B, respectively. The results of Aurora enzymes restrictive activities recommend that the synthesized compounds exert their anticancer activity by inhibiting aurora kinase inhibitors. Abstract : We have designed and synthesized novel tetrahydrodibenzo[b, g] [1, 8]naphthyridinone molecules by one‐pot synthesis, The synthesized compounds were biologically evaluated for anticancer activity against three cancer cells A549, HepG2, and HeLa using MTT assay by VX‐680 as standard drug, specifically inhibiting Aurora A and B kinases. The compound 4k was found to be the foremost potent anticancer compound among the all derivatives.